Optimal Design of Automotive Suspension Springs Using Differential Evolution Algorithm - Betül Sultan Yıldız (Uludağ University Journal of The Faculty of Engineering, 2018)
The automotive industry has been growing steadily and paying attention to develop technologies and production processes in the world. Automotive companies are facing great competition due to the increasing number of companies and the rapid increase in customer expectations as a result of developing technological products. In order to compete, automotive manufacturers need to meet the expectations of customers and governments, such as vehicle weight, collision safety, fuel emissions and vehicle comfort. In order to ensure that competition is sustainable, companies should design lighter and more efficient parts that require less processing costs with more precise operations. Recently, concerns about fuel consumption and air pollution have been reported. Meta-heuristic optimization methods have been widely used for optimization of vehicle component over the past three decades.  In this paper, differential evolution (DE) algorithm is used for optimization of the coil spring design, which is one of the suspension spring types. Using the DE algorithm, the mass of the coil spring decreased by about 29.3 %. The results show that the DE algorithm provides better solutions as previous methods in the literature.